2013
DOI: 10.1097/prs.0b013e3182a8077e
|View full text |Cite
|
Sign up to set email alerts
|

Foramen Magnum Size and Involvement of Its Intraoccipital Synchondroses in Crouzon Syndrome

Abstract: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…This study showed that the FM surface area is smaller in patients with different types of syndromic or complex craniosynostosis compared with control subjects, which is in line with studies reporting on patients with CrouzonePfeiffer syndrome (Coll et al, 2012;Rijken et al, 2013) and Muenke syndrome (Di Rocco et al, 2014). Moreover, we found that this difference is already present at birth and increases over time.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study showed that the FM surface area is smaller in patients with different types of syndromic or complex craniosynostosis compared with control subjects, which is in line with studies reporting on patients with CrouzonePfeiffer syndrome (Coll et al, 2012;Rijken et al, 2013) and Muenke syndrome (Di Rocco et al, 2014). Moreover, we found that this difference is already present at birth and increases over time.…”
Section: Discussionsupporting
confidence: 93%
“…While FGFR2 is highly expressed in both the osteogenic and chondrogenic cell lineage, FGFR3 is especially expressed in the proliferating chondrocytes. Therefore, these genes play a major role in skull base development and may induce premature fusion of Rijken et al, 2013;Tahiri et al, 2013). Although less is known about the influence of the TWIST1-gene on fusion of the skull base synchondroses in SaethreeChotzen patients, TWIST1 is important in morphogenesis of the cephalic neural tube (Soo et al, 2002) and promotes intramembranous ossification in the skull (Hermann et al, 2012) in mouse models.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…CNS: Abnormalities are common and include venous anomalies due to diversion of venous outflow through enlarged emissary veins, ventriculomegaly, tonsillar herniation due to the small skull base, and callosal dysgenesis (Fig ) …”
Section: Glossarymentioning
confidence: 99%